2023
DOI: 10.1094/pdis-09-22-2246-re
|View full text |Cite
|
Sign up to set email alerts
|

Linalool Induces Resistance Against Tobacco Mosaic Virus in Tobacco Plants

Abstract: The essential oil of Cinnamomum camphora is the most widely consumed and used spice in the world today. It has therapeutic effects in medicine and has been shown to have good antibacterial and bacteriostatic effects in agriculture. This study found that C. camphora oil significantly induced plant disease resistance activity. Linalool, its main active component, significantly induced plant disease resistance activity (67.49% at a concentration of 800 μg/ml) over the same concentration of the chitosan oligosacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Linalool, a monoterpene alcohol found in various EOs, has shown promising antimicrobial activity against a wide range of pathogens [13] . Our groups and other research teams have reported that linalool exhibits antimicrobial activity against bacteria such as Escherichia coli [12] , Listeria monocytogenes [14] , Elizabethkingia miricola , Streptococcus pyogenes [15] , Pseudomonas fragi [16] , staphylococcus aureus [17] , Brochothrix thermosphacta [18] and Aeromonas hydrophila [19] , as well as against oomycetes like Colletotrichum lagenarium [20] and Phytophthora capsici [21] , and fungi including Aspergillus flavus [22] , Penicillium citrinum , Chaetomium globosum [23] , Colletotrichum gloesporioides , Fusarium oxysporum [24] , Botrytis cinerea [25] and Candida albicans [26] . Although the antimicrobial activity of linalool has been extensively studied in vitro , the potential immune mechanism in vivo remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Linalool, a monoterpene alcohol found in various EOs, has shown promising antimicrobial activity against a wide range of pathogens [13] . Our groups and other research teams have reported that linalool exhibits antimicrobial activity against bacteria such as Escherichia coli [12] , Listeria monocytogenes [14] , Elizabethkingia miricola , Streptococcus pyogenes [15] , Pseudomonas fragi [16] , staphylococcus aureus [17] , Brochothrix thermosphacta [18] and Aeromonas hydrophila [19] , as well as against oomycetes like Colletotrichum lagenarium [20] and Phytophthora capsici [21] , and fungi including Aspergillus flavus [22] , Penicillium citrinum , Chaetomium globosum [23] , Colletotrichum gloesporioides , Fusarium oxysporum [24] , Botrytis cinerea [25] and Candida albicans [26] . Although the antimicrobial activity of linalool has been extensively studied in vitro , the potential immune mechanism in vivo remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%